Impact of Government Spending on Education, Infrastructure Investment, Health Expenditure, and Technology Investment on Economic Growth in Indonesia - Sangaji, Joko (West Science Business and Management, 2023)
This study examines how government expenditures on infrastructure, health care, education, and technology affect Indonesia's economic expansion. An analysis of Structural Equation Modeling - Partial Least Squares (SEM-PLS) was done using a quantitative methodology on a sample of 250 people that included academics, business representatives, government officials, and members of the general public. The structural model analysis showed a strong positive correlation between government spending on infrastructure, health, education, and technology and its effect on economic growth, while the measurement model evaluation validated the validity and reliability of the survey instrument. The model fit was deemed adequate based on the goodness-of-fit indices. The results highlight how important investments in technology and education are in promoting economic growth, with infrastructure and healthcare spending playing a major impact as well. These findings offer policymakers insightful information that supports a targeted, balanced approach to government spending for Indonesia's sustainable economic growth.